2020
DOI: 10.1186/s12955-020-01530-w
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life (EQ-5D + C) among people living in artisanal and small-scale gold mining areas in Zimbabwe: a cross-sectional study

Abstract: Background In Zimbabwe, an estimated 500,000 people work in the sector of artisanal and small-scale gold mining (ASGM). Two million Zimbabweans are dependent on this sector. Using mercury is common to extract gold from ore. Long term exposure to mercury can cause various adverse health conditions including chronic mercury intoxication. The influence of these adverse health effects on the health-related quality of life (HRQoL) is still unknown. The aim of this study is to assess the HRQoL of people who identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Therefore, the purpose of this study was the analysis of As and Cd in urine as well as Pb in blood samples collected during a cross-sectional study involving people that identified themselves as miners in two ASGM areas in Zimbabwe. Data on Hg levels and health-related quality of life from this study were published elsewhere (Butscher et al 2020;Mambrey et al 2020;Wahl et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the purpose of this study was the analysis of As and Cd in urine as well as Pb in blood samples collected during a cross-sectional study involving people that identified themselves as miners in two ASGM areas in Zimbabwe. Data on Hg levels and health-related quality of life from this study were published elsewhere (Butscher et al 2020;Mambrey et al 2020;Wahl et al 2021).…”
Section: Introductionmentioning
confidence: 99%